Interferon regulatory factor 5 gene polymorphism in Egyptian children with systemic lupus erythematosus. (July 2017) - Hammad, A; Mossad, Y M; Nasef, N; Eid, R
Background: Increased expression of interferon-inducible genes is implicated in the pathogenesis of systemic lupus erythematosus (SLE). Interferon regulatory factor 5 (IRF5) is one of the transcription factors regulating interferon and was proved to be implicated in the pathogenesis of SLE in different populations. Objectives: The objective of this study was to investigate the correlation between polymorphisms of the IRF5 gene and SLE susceptibility in a cohort of Egyptian children and to investigate their association with clinico-pathological features, especially lupus nephritis. Subjects and methods: Typing of interferon regulatory factor 5 rs10954213, rs2004640 and rs2280714 polymorphisms were done using polymerase chain reaction-restriction fragment length polymorphism for 100 children with SLE and 100 matched healthy controls. Results: Children with SLE had more frequent T allele and TT genotype of rs2004640 ( P c  = 0.003 and 0.024, respectively) compared to controls. Patients with nephritis had more frequent T allele of rs2004640 compared to controls ( P c  = 0.003). However the allele and genotype frequencies of the three studied polymorphisms did not show any difference in patients with nephritis in comparison to those without nephritis. Haplotype GTA of rs10954213, rs2004640 and rs2280714, respectively, was more frequent in lupus patients in comparison to controls ( p  = 0.01) while the haplotype GGG was more frequent in controls than lupus patients ( p  = 0.011). Conclusion: The rs2004640 T allele and TT genotype and GTA haplotype of rs rs10954213, rs2004640, and rs2280714, respectively, can be considered as risk factors for the development of SLE. The presence of the rs2004640 T allele increases the risk of nephritis development in Egyptian children with SLE.